Le système financier bas-canadien au tournant du XIXe siècle - Paquet, Gilles; Wallot, Jean-Pierre (L'Actualité économique)

(untitled) (HEC Montréal, 1983)
AbstractThis paper examines the evolution of the Canadian financial system from its embryonic form in New France to its modern contours in the first half of the 19th century. It is argued that the financial sub-system as a social technology experienced a mutation at the turn of the 19th century, as the result of unintended consequence of a combination of external, internal, and policy forces.